2012
DOI: 10.1371/journal.pone.0033756
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of the ORF5 Gene of Porcine Reproductive and Respiratory Syndrome Virus Isolates in Southwest China from 2007 to 2009

Abstract: To gain insight into the molecular epidemiology and possible mechanisms of genetic variation of porcine reproductive and respiratory syndrome (PRRS) in Yunnan Province of China, the ORF5 gene of 32 PRRSV isolates from clinical samples collected from 2007 to 2009 were sequenced and analyzed. Nucleotide and amino acid analyses were carried out on 32 isolates and representative strains of the North American genotype, European genotype and two representative Chinese isolates. Results reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Because PRRSV evolves very quickly [9,10], there is a great deal of genetic variability among PRRSV strains. In general, PRRSV strains are grouped into European (type 1) and North American (type 2) genotypes [11][12][13], but high levels of genetic variability still exist among viruses, even within the same genotype [10,14,15], which results in suboptimal cross-protection between different PRRSV strains and becomes a significant impediment to the development of effective vaccines. Modified live virus (MLV) vaccines have been most commonly used to control PRRSV because they confer better protection against homologous virus strains compared to inactivated or recombinant vaccines [16].…”
Section: Introductionmentioning
confidence: 99%
“…Because PRRSV evolves very quickly [9,10], there is a great deal of genetic variability among PRRSV strains. In general, PRRSV strains are grouped into European (type 1) and North American (type 2) genotypes [11][12][13], but high levels of genetic variability still exist among viruses, even within the same genotype [10,14,15], which results in suboptimal cross-protection between different PRRSV strains and becomes a significant impediment to the development of effective vaccines. Modified live virus (MLV) vaccines have been most commonly used to control PRRSV because they confer better protection against homologous virus strains compared to inactivated or recombinant vaccines [16].…”
Section: Introductionmentioning
confidence: 99%
“…Other representative amino acid mutations of the PNE (S37→P37, H38→Q38/Y38, L41→S41, Y43→C43, and G52→V52) were also found in these 89 isolates. It has been reported that ORF5 codon positions 13 and 151 played a key role in denaturing VR2332 to MLV RespPRRSV (Yin G, et al, 2009). In this study, Q13 was observed in 7 of 89 isolates (7.87%), while R13 was observed in the remaining 82 isolates (92.13%) (Supplementary Table 2).…”
Section: Recombination Occurred Due To Extensive Use Of the Representmentioning
confidence: 52%
“…GP5 is one of the structural proteins with the highest variability in PRRSV . As the main candidate protein for the development of vaccine subunits, also as a result of its immunological significance and polymorphic nature, GP5 has been the target for analysis of the genetic diversity of PRRSV (Yin G, et al, 2009). The results in this study showed that the length of deduced amino acids of 89 complete ORF5 of PRRSV ranged from 199 aa to 201 aa (Supplementary Table 1).…”
Section: Recombination Occurred Due To Extensive Use Of the Representmentioning
confidence: 83%
See 1 more Smart Citation
“…5 lineage viruses were identified in China – lineage 8.7 (Chinese HP‐PRRSV), lineage 5.1 (VR2332‐like), lineage 1 (NADC30‐like), lineage 9 (JX014356.1_XJNJ‐12‐1) and lineage 3 (GM2‐like; Gao et al, ; Shi, Lam, Hon, Murtaugh, et al, ). Epidemiological studies reported that lineage 3 viruses are endemic in China from some time (Cao et al, ; Wang et al, ; Xie et al, ; Yin et al, ). Recent evidence states that novel lineage 3 viruses with increased virulence emerged in south China (Dong et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%